Struktur Komposisi, Kelimpahan, dan Karakterisasi Morfologi Anggrek (Orchidaceae) di Hutan Desa Serdang Kawasan Tahura Kabupaten Karo Sumatera Utara - Suheriyana Aulia Pohan; Melfa Aisyah Hutasuhut; Kartika Manalu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the structural composition, abundance, and morphological characterization of orchids (Orchidaceae) in the Serdang Village Forest, Tahura area, Karo Regency, North Sumatra. The method used was an exploratory survey with a quadrat plot technique using purposive sampling. A total of 12 plots measuring 10 × 10 meters were randomly placed in the study area. The results showed that 360 individual Orchidaceae plants from 21 genera were found. The structure of Orchidaceae plants was analyzed based on the Importance Value Index (IVI), with the highest value observed in Neuwiedia zollingeri (30.77%), followed by Liparis ferruginea Lindl (19.89%) and Erythrodes blumei (Lindl.) Schltr (10.80%). The species diversity index in the study area was 2.66, which is categorized as moderate. The most abundant terrestrial orchid was Neuwiedia zollingeri (33.44%), while the most abundant epiphytic orchid was Adenoncos sumatrana with an RA of 13.04%. Epiphytic orchids were mostly found on host trees in zones III and IV. Morphological characterization identified 32 orchid species with morphological variations including leaf shape, leaf tip shape, flower shape, dorsal sepal shape, petal shape, tip shape of sepal and petal, dorsal sepal color pattern, petal color pattern, and root type. Keywords: Abundance, Morphological characterization, Orchidaceae, Structural composition